Existence of Several Pathotypes among Rice Yellow Mottle Virus (RYMV) Isolates Collected in Niger Republic - Issaka, S.; Onasanya, A.; Basso, A.; Sorho, F.; Haougui, A.; Sido, A.Y.; Ake, S.; Fargette, D.; Sere, Y (Science Alert, 2012)
This study has been conducted in screen house with an aim to asses the Rice yellow mottle virus pathogenic diversity and the level of resistance of released varieties in Niger republic. Sixty RYMV isolates from 23 Niger rice perimeters were inoculated mechanically to nine rice cultivars. The disease symptoms were scored at 42 days after inoculation. Analysis of Variance (ANOVA) and Additive Main effect and Multiplicative Interaction (AMMI) analysis were performed on the percentage of severity. The reaction of the rice cultivars to the virus isolates was significantly different. The interaction between isolates and rice cultivars was also significant. AMMI cluster analysis revealed the existence of four major pathotypes (Path 1 to 4) of Rice Yellow Mottle Virus (RYMV) in Niger republic. Path 4 pathotype included 12 resistance breaking isolates (20%). Path 3 and Path 2 pathotypes consist of 15 and 26 isolates respectively and were typical of wild type isolates with moderate level of pathogeny, including none aggressive (path 3 = MP) and aggressive isolates (Path 2 = MPA). The fourth pathotype Path 1 was made of 7 isolates and typical of particular isolates which have a moderate pathogenic level (FP). Resistance Breaking (RB) isolates occupied 30% of Niger rice ecologies in variable proportion. The rice varieties (Bassiroumo, IR15-29-690-3-1 and Kassoumo) released in Niger were highly susceptible to RYMV and therefore constituted a favorable condition for the rice yellow mottle disease propagation. This information is useful in rice breeding programs in the development and deployment of RYMV resistant cultivars to different rice perimeters in Niger Republic.